PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP PERILAKU KEAGAMAAN REMAJA DI KECAMATAN RILAU ALE KABUPATEN BULUKUMBA - Kamaluddin Tajibu (Fakultas Dakwah dan Komunikasi, 2021)
Instagram is a social media with a photo and video processing system and more practical information acquisition. Taking and distributing photos and videos with the features presented, it's no wonder that Instagram is the most popular social media. The advantages presented by Instagram social media are able to reach the most users of other social media, including teenagers, even the most users are teenagers.